Right to Information Act 2005 - A Review: Promoting Accountability and Transparent Governance (Journal of Advances and Scholarly Researches in Allied Education, 2019)
To ensure transparency in the administration, information must be made available to the people. Information and knowledge are instruments of transformation. Transparency, openness and accountability are the basic postulates to responsive, responsible and accountable government. In a welfare state, the functions and powers of the executive have grown manifolds in due course affecting every walk of life. Tackling the problem of high level political corruption in India has been a very important issue over which national debate is going on for the last many years. Somehow, incumbents have got the impression that they are unanswerable to any outside authority for their act of omission and commission.